2020
DOI: 10.1115/1.4046417
|View full text |Cite
|
Sign up to set email alerts
|

Physically Based Modeling of PEMFC Cathode Catalyst Layers: Effective Microstructure and Ionomer Structure–Property Relationship Impacts

Abstract: This work presents a pseudo-two-dimensional proton exchange membrane fuel cell (PEMFC) model incorporating Nafion ionomer structure–property relationships in the cathode catalyst layer (CL) to capture and explain losses at low Pt loading. Structural data from neutron reflectometry and thin film Nafion conductivity measurements predict variations in the oxygen diffusion coefficient and ionic conductivity with changing CL ionomer thickness and Pt loading. By including these structure–property relationships, pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…This implies that data from SiO 2 studies may still provide useful insight into CCL Nafion. Some of the present authors have previously presented similar hypotheses, using water uptake and reduced species mobilities inferred exclusively from Nafion on SiO 2 (from ref ) in physics-based models to predict PEMFC performance as a function of Pt loading. , Outcomes showed excellent agreement with low-Pt-loaded PEMFC polarization data, indicating the suitability of majority layer Nafion on silicon supports as a reasonable surrogate for that in the PEMFC CCL.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This implies that data from SiO 2 studies may still provide useful insight into CCL Nafion. Some of the present authors have previously presented similar hypotheses, using water uptake and reduced species mobilities inferred exclusively from Nafion on SiO 2 (from ref ) in physics-based models to predict PEMFC performance as a function of Pt loading. , Outcomes showed excellent agreement with low-Pt-loaded PEMFC polarization data, indicating the suitability of majority layer Nafion on silicon supports as a reasonable surrogate for that in the PEMFC CCL.…”
Section: Discussionsupporting
confidence: 64%
“…However, DeCaluwe et al demonstrated that reduced mobility is still present in homogeneously hydrated majority layers . Furthermore, modeling work from Randall and DeCaluwe displayed good agreement to data from low-Pt-loaded PEMFCs when the models incorporated ionomer structure–property relationships assuming uniformly hydrated CCL Nafion at carbon interfaces. , …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, many studies related to numerical simulation in the PEFCs have been reported. [4][5][6][7] Recently, a numerical analysis was performed on the electrochemical kinetics and mass transport inside porous materials. It was reported that the local saturation of liquid water, distribution of the electrochemical variables, and mass fraction of samples could be controlled by regulating the operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Toward this end, several recipes for catalyst ink dispersions have been tuned for optimum kinetic and thermodynamic performance [9][10][11][12][13][14]. The cathode of a high-power density PEMFC is typically made of a catalyst ink consisting of carbon black (C), forming an extensive skeleton.…”
Section: Introductionmentioning
confidence: 99%